Nature-Based Learning Media in Outdoor the Classroom to Increase Kindergarten Children's Learning Motivation - Murniati (Journal of Psychology and Instruction, 2022)
The lack of use of instructional media by teachers has an impact on low student motivation in learning. The purpose of this research is to get a strategy that can be done to increase students' learning motivation. The research method used in this study was research and development (R&D) with group B children in the Flamboyan PAUD Cluster unit. Data collection techniques used are interviews, observations, questionnaires, and documentation. After obtaining the data, the researcher then tested the validity of the data, namely the validity test and the reliability test. The next step is to analyze the data, analyze the feasibility of the model obtained from validator experts, both media experts and material experts, and obtained from teacher responses and children's responses and analysis of the model's effectiveness. Based on the analysis results, it shows that the development of outdoor learning media is suitable for use in learning. Based on the children's cognitive abilities it is increased after treatment using the development of outdoor learning media based on nature with a repeating pattern.